Evaluasi Kualitas Layanan Website Dinas Koperasi UMKM Kota Palembang Menggunakan Metode Webqual 4.0 - Fitria Azzahra; Vany Alia Putri; Agung Prayoga; Fenny Purwani (Journal of Information Systems and Business Technology, 2025)
This study evaluates the quality of the Palembang City MSME Cooperative Office website using the WebQual 4.0 method, which encompasses three main dimensions: usability, information quality, and service interaction quality. Data were collected through an online survey of 50 respondents, consisting of MSME actors and members of the public who had accessed the website in the last three months. The findings indicate that the usability aspect of the website is generally well perceived, particularly in terms of ease of navigation, clarity of layout, and accessibility across various devices. The service interaction dimension was also rated positively, with users acknowledging that the available online service features are functional and sufficiently helpful. However, the information quality dimension still requires considerable improvement, as several respondents noted issues related to outdated content, insufficient detail, and inaccuracies in the information presented. These shortcomings reduce the website’s effectiveness as a reliable source of official information. Based on these results, the study recommends increasing the frequency of content updates, enhancing the relevance and accuracy of information, and improving digital service features to better support user needs and ensure the website functions optimally as a public service platform.